Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Certainly! Let's solve the problem step-by-step.
### Part a: Generating the first six terms of the sequence
The sequence is defined as:
[tex]\[ a_1 = 2 \][/tex]
[tex]\[ a_{n+1} = \frac{1}{2} \left(a_n + 4 \right) \][/tex]
Let's calculate the first six terms.
1. For [tex]\( n = 1 \)[/tex]:
[tex]\[ a_1 = 2 \][/tex]
2. For [tex]\( n = 2 \)[/tex]:
[tex]\[ a_2 = \frac{1}{2} \left(a_1 + 4 \right) = \frac{1}{2} \left(2 + 4 \right) = \frac{1}{2} \times 6 = 3 \][/tex]
3. For [tex]\( n = 3 \)[/tex]:
[tex]\[ a_3 = \frac{1}{2} \left(a_2 + 4 \right) = \frac{1}{2} \left(3 + 4 \right) = \frac{1}{2} \times 7 = 3.5 \][/tex]
4. For [tex]\( n = 4 \)[/tex]:
[tex]\[ a_4 = \frac{1}{2} \left(a_3 + 4 \right) = \frac{1}{2} \left(3.5 + 4 \right) = \frac{1}{2} \times 7.5 = 3.75 \][/tex]
5. For [tex]\( n = 5 \)[/tex]:
[tex]\[ a_5 = \frac{1}{2} \left(a_4 + 4 \right) = \frac{1}{2} \left(3.75 + 4 \right) = \frac{1}{2} \times 7.75 = 3.875 \][/tex]
6. For [tex]\( n = 6 \)[/tex]:
[tex]\[ a_6 = \frac{1}{2} \left(a_5 + 4 \right) = \frac{1}{2} \left(3.875 + 4 \right) = \frac{1}{2} \times 7.875 = 3.9375 \][/tex]
So, the first six terms of the sequence are:
[tex]\[ \{2, 3, 3.5, 3.75, 3.875, 3.9375\} \][/tex]
### Part b: Proving that [tex]\(a_n < 4\)[/tex] for all [tex]\(n\)[/tex]
We will prove this statement by induction.
Base case:
For [tex]\( n = 1 \)[/tex],
[tex]\[ a_1 = 2 \][/tex]
Clearly, [tex]\( 2 < 4 \)[/tex], so the base case holds.
Inductive step:
Assume [tex]\( a_n < 4 \)[/tex] for some [tex]\( n \)[/tex]. We need to show that [tex]\( a_{n+1} < 4 \)[/tex].
From the recursive definition, we have:
[tex]\[ a_{n+1} = \frac{1}{2} \left(a_n + 4 \right) \][/tex]
Since [tex]\( a_n < 4 \)[/tex], let [tex]\( a_n = 4 - \epsilon \)[/tex], where [tex]\( \epsilon > 0 \)[/tex]. Then,
[tex]\[ a_{n+1} = \frac{1}{2} \left((4 - \epsilon) + 4 \right) = \frac{1}{2} \left(8 - \epsilon \right) = 4 - \frac{\epsilon}{2} \][/tex]
Since [tex]\( \epsilon > 0 \)[/tex], it follows that [tex]\( 4 - \frac{\epsilon}{2} < 4 \)[/tex]. Hence,
[tex]\[ a_{n+1} < 4 \][/tex]
By induction, we have proven that [tex]\( a_n < 4 \)[/tex] for all [tex]\( n \)[/tex].
### Part c: Proving that [tex]\(\{ a_n \}\)[/tex] is a monotonically increasing sequence
We want to show that [tex]\( a_{n+1} \ge a_n \)[/tex] for all [tex]\( n \)[/tex].
Using the recursive definition:
[tex]\[ a_{n+1} = \frac{1}{2} \left(a_n + 4 \right) \][/tex]
Let's examine the difference [tex]\( a_{n+1} - a_n \)[/tex]:
[tex]\[ a_{n+1} - a_n = \frac{1}{2} \left(a_n + 4 \right) - a_n \][/tex]
[tex]\[ = \frac{1}{2} a_n + 2 - a_n \][/tex]
[tex]\[ = 2 - \frac{1}{2} a_n \][/tex]
Since [tex]\( a_n < 4 \)[/tex], let [tex]\( a_n = 4 - \epsilon \)[/tex] where [tex]\( \epsilon > 0 \)[/tex]. Then,
[tex]\[ 2 - \frac{1}{2} a_n = 2 - \frac{1}{2} (4 - \epsilon) = 2 - 2 + \frac{\epsilon}{2} = \frac{\epsilon}{2} \][/tex]
Since [tex]\( \epsilon > 0 \)[/tex], it follows that [tex]\( \frac{\epsilon}{2} > 0 \)[/tex]. Therefore,
[tex]\[ a_{n+1} - a_n = \frac{\epsilon}{2} > 0 \][/tex]
Thus, we have [tex]\( a_{n+1} > a_n \)[/tex], proving that the sequence [tex]\(\{ a_n \}\)[/tex] is monotonically increasing.
### Conclusion
a) The first six terms of the sequence are [tex]\(\{ 2, 3, 3.5, 3.75, 3.875, 3.9375 \}\)[/tex].
b) We proved that [tex]\( a_n < 4 \)[/tex] for all [tex]\( n \)[/tex].
c) We also proved that the sequence [tex]\(\{ a_n \}\)[/tex] is monotonically increasing.
### Part a: Generating the first six terms of the sequence
The sequence is defined as:
[tex]\[ a_1 = 2 \][/tex]
[tex]\[ a_{n+1} = \frac{1}{2} \left(a_n + 4 \right) \][/tex]
Let's calculate the first six terms.
1. For [tex]\( n = 1 \)[/tex]:
[tex]\[ a_1 = 2 \][/tex]
2. For [tex]\( n = 2 \)[/tex]:
[tex]\[ a_2 = \frac{1}{2} \left(a_1 + 4 \right) = \frac{1}{2} \left(2 + 4 \right) = \frac{1}{2} \times 6 = 3 \][/tex]
3. For [tex]\( n = 3 \)[/tex]:
[tex]\[ a_3 = \frac{1}{2} \left(a_2 + 4 \right) = \frac{1}{2} \left(3 + 4 \right) = \frac{1}{2} \times 7 = 3.5 \][/tex]
4. For [tex]\( n = 4 \)[/tex]:
[tex]\[ a_4 = \frac{1}{2} \left(a_3 + 4 \right) = \frac{1}{2} \left(3.5 + 4 \right) = \frac{1}{2} \times 7.5 = 3.75 \][/tex]
5. For [tex]\( n = 5 \)[/tex]:
[tex]\[ a_5 = \frac{1}{2} \left(a_4 + 4 \right) = \frac{1}{2} \left(3.75 + 4 \right) = \frac{1}{2} \times 7.75 = 3.875 \][/tex]
6. For [tex]\( n = 6 \)[/tex]:
[tex]\[ a_6 = \frac{1}{2} \left(a_5 + 4 \right) = \frac{1}{2} \left(3.875 + 4 \right) = \frac{1}{2} \times 7.875 = 3.9375 \][/tex]
So, the first six terms of the sequence are:
[tex]\[ \{2, 3, 3.5, 3.75, 3.875, 3.9375\} \][/tex]
### Part b: Proving that [tex]\(a_n < 4\)[/tex] for all [tex]\(n\)[/tex]
We will prove this statement by induction.
Base case:
For [tex]\( n = 1 \)[/tex],
[tex]\[ a_1 = 2 \][/tex]
Clearly, [tex]\( 2 < 4 \)[/tex], so the base case holds.
Inductive step:
Assume [tex]\( a_n < 4 \)[/tex] for some [tex]\( n \)[/tex]. We need to show that [tex]\( a_{n+1} < 4 \)[/tex].
From the recursive definition, we have:
[tex]\[ a_{n+1} = \frac{1}{2} \left(a_n + 4 \right) \][/tex]
Since [tex]\( a_n < 4 \)[/tex], let [tex]\( a_n = 4 - \epsilon \)[/tex], where [tex]\( \epsilon > 0 \)[/tex]. Then,
[tex]\[ a_{n+1} = \frac{1}{2} \left((4 - \epsilon) + 4 \right) = \frac{1}{2} \left(8 - \epsilon \right) = 4 - \frac{\epsilon}{2} \][/tex]
Since [tex]\( \epsilon > 0 \)[/tex], it follows that [tex]\( 4 - \frac{\epsilon}{2} < 4 \)[/tex]. Hence,
[tex]\[ a_{n+1} < 4 \][/tex]
By induction, we have proven that [tex]\( a_n < 4 \)[/tex] for all [tex]\( n \)[/tex].
### Part c: Proving that [tex]\(\{ a_n \}\)[/tex] is a monotonically increasing sequence
We want to show that [tex]\( a_{n+1} \ge a_n \)[/tex] for all [tex]\( n \)[/tex].
Using the recursive definition:
[tex]\[ a_{n+1} = \frac{1}{2} \left(a_n + 4 \right) \][/tex]
Let's examine the difference [tex]\( a_{n+1} - a_n \)[/tex]:
[tex]\[ a_{n+1} - a_n = \frac{1}{2} \left(a_n + 4 \right) - a_n \][/tex]
[tex]\[ = \frac{1}{2} a_n + 2 - a_n \][/tex]
[tex]\[ = 2 - \frac{1}{2} a_n \][/tex]
Since [tex]\( a_n < 4 \)[/tex], let [tex]\( a_n = 4 - \epsilon \)[/tex] where [tex]\( \epsilon > 0 \)[/tex]. Then,
[tex]\[ 2 - \frac{1}{2} a_n = 2 - \frac{1}{2} (4 - \epsilon) = 2 - 2 + \frac{\epsilon}{2} = \frac{\epsilon}{2} \][/tex]
Since [tex]\( \epsilon > 0 \)[/tex], it follows that [tex]\( \frac{\epsilon}{2} > 0 \)[/tex]. Therefore,
[tex]\[ a_{n+1} - a_n = \frac{\epsilon}{2} > 0 \][/tex]
Thus, we have [tex]\( a_{n+1} > a_n \)[/tex], proving that the sequence [tex]\(\{ a_n \}\)[/tex] is monotonically increasing.
### Conclusion
a) The first six terms of the sequence are [tex]\(\{ 2, 3, 3.5, 3.75, 3.875, 3.9375 \}\)[/tex].
b) We proved that [tex]\( a_n < 4 \)[/tex] for all [tex]\( n \)[/tex].
c) We also proved that the sequence [tex]\(\{ a_n \}\)[/tex] is monotonically increasing.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.